Internet of Things (IoT) based counsellor skills 21st century - Suryawati, Citra Tectona; Susilo, Agus Tri; Purwaningrum, Ribut; Asrowi, Asrowi (Universitas Islam Negeri Raden Intan Lampung, 2021)
The rapid development of the era requires guidance and counseling teachers to be more creative in providing services. The purpose of this study is to determine the level of 21st century skills based on the Internet of Things (IoT) based on categorization. The sample of this study was 53 people consisting of school counselors in Sukoharjo and students of professional education and counselling teachers at one university. The method used is a one-shot case study. The results showed that the average 21st century counsellor's skills of 54.3% were in the 'medium' category. This can be interpreted that the skills of 21st century counsellor when participating in IoT-based skills development workshops have good criteria. However, it is possible that there is a need to improve skills again so that the quality of guidance and counselling services is getting better and more effective.